Adverse pregnancy outcomes and associated risk factors among pregnant women with syphilis during 2013–2018 in Hunan, China - Gao, Jie; Chen, Xia; Yang, Min; Wu, Yinglan; Liang, Ting; Li, Huixia; Xie, Wanqin (Frontiers in Medicine, 2023)
Objective To investigate the adverse pregnancy outcomes and associated risk factors among pregnant women with syphilis. Design Pregnant women with syphilis in the registry for the prevention of mother-to-child transmission of AIDS, syphilis and hepatitis B in Hunan Province, China, from January 1, 2013 to December 31, 2018 were included in the study. Results Among the 14,219 pregnant women with syphilis, 11,346 had definite pregnancy outcomes and were in singleton pregnancy. The risk factors related to adverse pregnancy outcomes include the age of pregnant women with syphilis <20 years old (aOR = 1.274, 95% CI: 1.088–1.493) or ≥ 35 years old (aOR = 1.402, 95% CI: 1.167–1.686), not married (aOR = 1.855, 95% CI: 1.453–2.367), initial syphilis detection in the late pregnancy (aOR = 1.266, 95% CI: 1.032–1.555), diagnosis of syphilis in the late pregnancy (aOR = 5.806, 95% CI: 1.796–18.770), diagnosis of syphilis during labor (aOR = 4.102, 95% CI: 1.263–13.330), husband/sexual partner infected with syphilis (aOR = 1.222, 95% CI: 1.068–1.398), untreated (aOR = 6.756, 95% CI: 5.586–8.197), and nonstandard medication (aOR = 3.300, 95% CI: 2.841–3.846). Conclusion The prevalence of adverse pregnancy outcomes among pregnant women with syphilis in Hunan Province, China from 2013 to 2018 was relatively high. The adverse pregnancy outcomes associated with syphilis could be reduced by early detection and standard treatment of syphilis for pregnant women and their husbands/sexual partners.